2015
DOI: 10.1038/srep11049
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte specific responses to soluble and mechanical stimuli in a stem cell derived culture model

Abstract: Studying osteocyte behavior in culture has proven difficult because these embedded cells require spatially coordinated interactions with the matrix and surrounding cells to achieve the osteocyte phenotype. Using an easily attainable source of bone marrow mesenchymal stem cells, we generated cells with the osteocyte phenotype within two weeks. These “stem cell derived-osteocytes” (SCD-O) displayed stellate morphology and lacunocanalicular ultrastructure. Osteocytic genes Sost, Dmp1, E11, and Fgf23 were maximall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 44 publications
0
48
1
1
Order By: Relevance
“…In contrast to our results, Lau et al reported an approximately 30% reduction in RANKL gene expression in osteocyte‐like cells after 1 h of vibration (0.3 g, 30 Hz) . In another study using stem‐cell‐derived‐osteocytes, no effect on RANKL expression was found with 2 days of vibration exposure (0.7 g, 90 Hz, 20 min/day) . One possible explanation for this discrepancy can be the different exposure time administered to the cells.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, Lau et al reported an approximately 30% reduction in RANKL gene expression in osteocyte‐like cells after 1 h of vibration (0.3 g, 30 Hz) . In another study using stem‐cell‐derived‐osteocytes, no effect on RANKL expression was found with 2 days of vibration exposure (0.7 g, 90 Hz, 20 min/day) . One possible explanation for this discrepancy can be the different exposure time administered to the cells.…”
Section: Discussioncontrasting
confidence: 99%
“…53 In another study using stem-cell-derived-osteocytes, no effect on RANKL expression was found with 2 days of vibration exposure (0.7 g, 90 Hz, 20 min/day). 54 One possible explanation for this discrepancy can be the different exposure time administered to the cells. A decreased RANKL expression was also observed in our study after day 1 of vibration exposure (data not shown).…”
Section: Administration Duration Influences the Effectsmentioning
confidence: 99%
“…2E). In fact, osteocytic genes shared with MSC-B7 and MSC-B15 cells were further increased in the MSC-B15 cells, suggesting that by day 15, the MSCs were either progressing toward or had become osteocytes, as recently suggested (39). Interestingly, gremlin-1 (Grem1) expression was identified following osteoblast differentiation; Grem1-positive MSCs are hypothesized to be unable to differentiate into adipocytes (40).…”
Section: Marrow-derived Mscs Differentiate Into Mature Adipocytes Andmentioning
confidence: 72%
“…Osteocytes, the mechanosensors in bone, have also been demonstrated to be affected by LMHF vibration. For instance, the gap junctional communication of MLO‐Y4 osteocytes is amplified by low‐intensity vibration (Uzer et al, ), and the expression of some osteocyte markers, such as sclerostin and RANKL, was also changed after low‐magnitude vibration (Lau et al, ; Thompson et al, ). Moreover, the osteoclasts resorption is inhibited by the control medium of vibrated osteocytes (Lau et al, ).…”
Section: Introductionmentioning
confidence: 99%